2015
DOI: 10.2215/cjn.05410514
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Neutral-pH, Low–Glucose Degradation Product Peritoneal Dialysis Solutions on Residual Renal Function, Urine Volume, and Ultrafiltration

Abstract: Background and objectives Neutral-pH, low-glucose degradation products solutions were developed in an attempt to lessen the adverse effects of conventional peritoneal dialysis solutions. A systematic review was performed evaluating the effect of these solutions on residual renal function, urine volume, peritoneal ultrafiltration, and peritoneal small-solute transport (dialysate to plasma creatinine ratio) over time.Design, setting, participants, & measurements Multiple electronic databases were searched from J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 34 publications
(28 reference statements)
5
39
0
4
Order By: Relevance
“…However, the beneficial effects on RRF were mixed in a greater number of later studies and trials [75][76][77][78] . Yohanna et al [79] systematically reviewed 11 trials in which 643 patients were included. They reported that the use of a neutral-pH, low-GDP solution resulted in better preserved RRF after various study periods.…”
Section: Dialysis Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the beneficial effects on RRF were mixed in a greater number of later studies and trials [75][76][77][78] . Yohanna et al [79] systematically reviewed 11 trials in which 643 patients were included. They reported that the use of a neutral-pH, low-GDP solution resulted in better preserved RRF after various study periods.…”
Section: Dialysis Techniquesmentioning
confidence: 99%
“…The conclusion is that the use of a neutral-pH, low-GDP solution results in better preservation of RRF. However, whether the biocompatible solutions can benefit the long-term clinical outcomes of patients cannot be predicted at present [79][80][81] .…”
Section: Dialysis Techniquesmentioning
confidence: 99%
“…These ultrastructural findings might be linked not only to former pathological studies [16,[91][92][93] but also to clinical findings following the use of biocompatible solutions, for example, preserved UF capacity despite increasing small solute transport [94,95]. However, the impact on peritoneal membrane transport function has not been quantified by meta-analysis [96][97][98]. Last but not least, biocompatible PD solution is not fully biocompatible, and still needs to be improved to counter unsolved problems such as infection, PD membrane preservation, and patient survival (for review [57]).…”
Section: Pathological Findings Of Pd Associated Infectious Peritonitismentioning
confidence: 99%
“…Furthermore, based on two systematic reviews and meta‐analyses of randomized controlled trials, the ISPD guidelines recently provided a weak grade (2B) recommendation for biocompatible solutions for the purpose of preserving residual renal function when used for more than 12 months . Three subsequently published systematic reviews have further confirmed that biocompatible solutions preserve residual renal function better than conventional solutions, with one systematic review demonstrating a benefit within the first 12 months …”
Section: Improving Patient Outcomesmentioning
confidence: 99%